Bodily distress syndrome: A new diagnosis for functional disorders in primary care?. Issue 1 (December 2015) - Budtz-Lilly, Anna; Schröder, Andreas; Rask, Mette; Fink, Per; Vestergaard, Mogens; Rosendal, Marianne
Abstract Background Conceptualisation and classification of functional disorders appear highly inconsistent in the health-care system, particularly in primary care. Numerous terms and overlapping diagnostic criteria are prevalent of which many are considered stigmatising by general practitioners and patients. The lack of a clear concept challenges the general practitioner's decision-making when a diagnosis or a treatment approach must be selected for a patient with a functional disorder. This calls for improvements of the diagnostic categories. Intense debate has risen in connection with the release of the fifth version of the 'Diagnostic and Statistical Manual of Mental Disorders' and the current revision of the 'International Statistical Classification of Diseases and Related Health Problems'. We aim to discuss a new evidence based diagnostic proposal, bodily distress syndrome, which holds the potential to change our current approach to functional disorders in primary care. A special focus will be directed towards the validity and utility criteria recommended for diagnostic categorisation. Discussion A growing body of evidence suggests that the numerous diagnoses for functional disorders listed in the current classifications belong to one family of closely related disorders. We name the underlying phenomenon 'bodily distress'; it manifests as patterns of multiple and disturbing bodily sensations. Bodily distress syndrome is a diagnostic category with specific criteria covering this illness phenomenon. The category has been explored through empirical studies, which in combination provide a sound basis for determining a symptom profile, the diagnostic stability and the boundaries of the condition. However, as bodily distress syndrome embraces only the most common symptom patterns, patients with few but impairing symptoms are not captured. Furthermore, the current lack of treatment options may also influence the acceptance of the proposed diagnosis. Summary Bodily distress syndrome is a diagnostic category with notable validity according to empirical studies. Nevertheless, knowledge is sparse on the utility in primary care. Future intervention studies should investigate the translation of bodily distress syndrome into clinical practice. A particular focus should be directed towards the acceptability among general practitioners and patients. Most importantly, it should be investigated whether the new category may provide the basis for better treatment and improved clinical outcome.